Improving Employee Performance Through Teamwork as an Effort to Create a Solid Organization - Yopie Alfiani (MultiTech Publisher, 2024)
Teamwork is a component inherent in each individual which is based on the experiences, actions and feelings of each team member which are interconnected in achieving task goals, as well as implementing performance in an organization. This is what makes the writer do research. The aim of this research is to determine the influence between teamwork on employee performance at the Swadharma Jakarta Cooperative. This research uses a quantitative descriptive method with data collection techniques through distributing questionnaires and library data. This research used a saturated sampling method of 50 employees at the Swadharma Jakarta Cooperative with a simple linear regression data analysis technique. The results of this research show that there is a partial influence between teamwork on employee performance at the Swadharma Jakarta Cooperative. It is hoped that the results of this research will contribute to further research.